Synthesis and Crystal Structure of 1-(4-[(E)-4-methoxy-2-hydroxybenzylidene]aminophenyl)ethanoe Oxime - Dong, Wen-Kui; Wu, Jun-Jiang; Wang, Li; Zhang, Yang; Li, Xiang; Li, Li (Asian Journal of Chemistry, 2013)
The compound 1-(4-[(E)-4-methoxy-2-hydroxybenzylidene]aminophenyl)ethanoe oxime with the molecular formula C16H16N2O3, has been synthesized and characterized structurally. The two benzene rings in the molecule form a dihedral angle of 3.05(2)º. There is one strong intramolecular O-H···N hydrogen bond between the hydroxyl (O2-H2) groups and the Schiff base nitrogen (N2) atom, with the distance of d(N2-O2) = 2.593(4) Å. In the crystal structure, each molecule links other three molecules into an infinite 2D supramolecular structure by three pairs of intermolecular O1-H1···N1, C1-H1A···O1 and C16-H16B···O3 hydrogen bonds.